Systematics And Distribution Of The Subfamily Coreinae (Heteroptera: Coreidae) Of Sarawak - Arif Akmal, Azman (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study records and discusses the entomological collection in Sarawak, with reference to voucher specimens of the subfamily Coreinae (l-leteroptera: Coreidae) in Sarawak Forestry Research Centre, Sarawak Biodiversity Centre, Semongok Agriculture Research Centre, and UNIMAS Insect Reference Collection. A total of 140 specimens, comprising 17 species from 11 genera were evaluated. The genus Mictis dominated other genera in composition of species with 17.6% domination followed by Physomerus, Dasynus, Homoeocerus, and Cletuswith 11.8% each. Systematics accounts of every species and distribution maps of the species examined are presented. Among the Coreinae in Sarawak, Mictis longicornis was found to be the most abundant species with 3 I individuals (22% of the total individuals) represented in the voucher collections. Most of the species of Coreinae known to occur in Sarawak were found in the terrestrial forest. Tachyco/pura penicif!ata and Cletus bipunctatuscould be considered as the rarest species of coreid in Sarawak being represented by one individual each. Distribution mapping of the species shows that Coreinae of Sarawak is distributed throughout the state.